Effective Indigenous Terminology in Canadian Legal Research for the Arctic ... - Hoffman, Nadine (University of Calgary, 2017)
Presented at the International Congress of Arctic Social Sciences in Umeå, Sweden as part of the International Arctic Social Sciences Association. This paper was part of the "Facilitating social sciences and humanities scholarship of the Arctic through library, archival and information services" session under the Research Methodologies conference theme. Thank you to the Calgary Law Libraries Group for the Education Grant to help cover travel costs. ... : Terms used in today’s society to describe Indigenous Peoples and cultures are significantly different than historical terminology. Contemporary Arctic and Indigenous researchers will know current keywords to conduct their research, but may not be able to locate historical documents if they are not cognizant of the changing terms used throughout history. This paper will analyze appropriate contemporary and historical keywords in the context of Canadian legal research best practices. Keywords used to effectively find Aboriginal resources will illustrate changes in taxonomy reflecting changes in societal norms, database practices, legal definitions, and the various jurisdictions of Aboriginal Peoples. A survey of Canadian law libraries will be conducted to analyze subject headings found in library catalogues, legal indexes, and other primary and secondary resources. Given the interdisciplinary nature of law, this paper will be applicable to most Indigenous scholars across the Social Sciences and Humanities. ...